Issues in vaccinology: Present challenges and future directions - Sheerin, D; Openshaw, PJ; Pollard, AJ (Wiley, 2017)
Vaccination is a principal and highly cost-effective means of controlling infectious diseases, providing direct protection against pathogens by conferring long-lasting immunological memory and inducing population-level herd immunity. Despite rapid ongoing progress in vaccinology, there remain many obstacles to the development and deployment of novel or improved vaccines; these include the underlying science of how to induce and sustain appropriate protective immune responses as well as bureaucratic, logistic and socio-political hurdles. The failure to distribute and administer existing vaccines to at-risk communities continues to account for a large proportion of infant mortality worldwide: almost 20 million children do not have access to basic vaccines and several million still die each year as a result. While emerging epidemic or pandemic diseases pose a significant threat to global health and prosperity, there are many infectious diseases which provide a continuous or cyclical burden on healthcare systems which also need to be addressed. Gaps in knowledge of the human immune system stand in the way of developing technologies to overcome individual and pathogenic variation. The challenges in tackling infectious disease and directions that the field of preventive medicine may take to improve the current picture of global health are the focus of this review. This article is protected by copyright. All rights reserved.